Análisis de los efectos de los contenidos televisivos y su influencia en el comportamiento de los adolescentes del Recinto El Jobo cantón Ventanas, año 2021 - Magayón Franco, Jomira Jaritza (2021)
The present research was carried out in the Canton Ventanas with the purpose of analyzing the effects of television content and its influence on the behavior of adolescents. It is hoped that, through this project, obtain a better behavior in these young people and achieve in them be better in everyday life. In the theoretical support, it is subjected to the variables of the problem that demonstrate its accuracy, carrying out a sustainable case study. The methodology used is qualitative and the research was descriptive, the technique that was developed for the collection of data and information was a virtual survey through google form to adolescents from the campus of Jobo canton Ventanas. The conclusions presented indicate that the behavior of adolescents is essential in them in society, where techniques that help in the conduct and improve behavior of adolescents in this community should be adopted.